2022
DOI: 10.1108/srj-05-2021-0181
|View full text |Cite
|
Sign up to set email alerts
|

Who should hold the baton of aviation sustainability?

Abstract: Purpose In the past four decades, substantial air traffic growth has triggered enthusiasm in the aviation sector. At the same time, this growth has posed challenges to its financial and environmental sustainability commitments. A buzz has been centered on introducing and supporting aviation sustainability initiatives. These challenges have led to acknowledging the need to reduce aviation fuel consumption, a function of multiple factors. The different stakeholders having a diverse type of interplay govern the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The review of BWM literature discloses its wide application (Mi et al , 2019; Singh et al , 2022). The BWM has been successfully used in various studies for addressing issues such as supplier segmentation, sustainability, risk management, identifying technology enablers, efficiency evaluation of university-industry PhD projects, evaluation of scientific outputs, firms’ R&D evaluation, selection of biomass conversion technology, selection of residential grid storage technology, selection of electric vehicle, green human resource management and for other applications.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The review of BWM literature discloses its wide application (Mi et al , 2019; Singh et al , 2022). The BWM has been successfully used in various studies for addressing issues such as supplier segmentation, sustainability, risk management, identifying technology enablers, efficiency evaluation of university-industry PhD projects, evaluation of scientific outputs, firms’ R&D evaluation, selection of biomass conversion technology, selection of residential grid storage technology, selection of electric vehicle, green human resource management and for other applications.…”
Section: Methodsmentioning
confidence: 99%
“…The review of BWM literature discloses its wide application (Mi et al, 2019;Singh et al, 2022) Considering the advantages and rising popularity, BWM is deemed fit to compute the weightage and rank the SC resilience strategies. In BWM, the distinctive structure is obtained by comparing best and other attributes and other attributes and worst attributes (Rezaei, 2015(Rezaei, , 2016 using a scale of 1-9 (Table 3), as exhibited in supplementary file Appendix A and Figure A2.…”
Section: Best-worst Methodsmentioning
confidence: 99%
“…During 2018-20, as many as 4,690 people were arrested under the UAPA but only 3 percent were convicted. Just as the Supreme Court is ready to examine the application of this law, while referring to the Naxal (violent Communist faction) menace, Prime Minister Modi declared that in fact the law provided great impetus to the fight against the gun and the pen (terrorism and fake news whipping up emotions, respectively) declared (Singh, 2022). Table 3 reflects the increase in these cases from 2015 to 2019.…”
Section: Suppress Dissentmentioning
confidence: 99%
“…However, these developments and suggestions alone cannot effectively address the sustainability challenge. [ 20 , 21 , 22 , 23 ] Gössling and Lyle [ 20 ] claim that it is possible to decrease aviation emissions, but achieving this goal necessitates policy measures either on a national scale or within regional entities like the European Union. Singh, Rana, Hamid, and Gupta [ 21 ] extensively analyzed different decision‐making levels to gain insights into the possibilities and prerequisites associated with promoting sustainability in aviation by tactical level and operational level decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 20 , 21 , 22 , 23 ] Gössling and Lyle [ 20 ] claim that it is possible to decrease aviation emissions, but achieving this goal necessitates policy measures either on a national scale or within regional entities like the European Union. Singh, Rana, Hamid, and Gupta [ 21 ] extensively analyzed different decision‐making levels to gain insights into the possibilities and prerequisites associated with promoting sustainability in aviation by tactical level and operational level decisions. The study concluded that decisions at the tactical level had the highest impact on reducing aviation fuel consumption, followed by decisions at the operational level and decisions at the strategic level.…”
Section: Literature Reviewmentioning
confidence: 99%